Las ocupaciones preocoloniales de cantón Guano, provincia de Chimborazo. Una mirada arqueológica hacia el territorio Puruhá e Incaico - Meléndrez Lara, María José (2022)
This research project analyzes and the pre-Columbian occupations base don samples found in the archaeoligcal settlements of the Puruha and Inca at Guano canton, Chimborazo province. Considering that Guano is an important archeological territory thanks to multiple archaeological excavations carried out at the beginning of the 20th century, in which a large quantity of pottery belonging to the Puruha culture were found, showing singns of pre- Hispanic settlement in the under- study area. The research conducted is the academic nature type, so the techniques used in this study are bibliographic reviews, direct observations and interviews with people who know the history of Guano and who have worked in the Ministry of Culture and the National Government. Institute if cultural heritage to obtain relevant information obtained, it is possible to know that the space that are maned in history are highly deteriorated due to the huaquerismo that has been carried out for years, which has led to the destruction of cultural heritage assets and the archaeological descontextualización of the Canton. Thus, this research puts into context the identification of the social occupations of the archaeological sites in different áreas of the Canton and their cultural styles. Among the results, it has been confirmed that there was a singular presence of the Puruhaes and Incas in Guaneño territory, these places with archaeological history are important to the expets and specialist in the subject of study, Thus, it is understood that archeological heritage is the essential testimony of past human activities, its protection and prponer management are essential to allow archeologists and scientists to study and interpret i ton hahalf of present and future generations and increase the knowledge of it.